2022
DOI: 10.1039/d2bm00076h
|View full text |Cite|
|
Sign up to set email alerts
|

A novel nano delivery system targeting different stages of osteoclasts

Abstract: Osteoclast(OC) abnormalities represent osteoporosis's critical mechanism (OP). OCs undergo multiple processes that range from monocytic to functional. Different drugs target OCs at different developmental stages; however, almost no Suitable drug-targeted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…As a result, protecting polyphenols in vivo and delivery to the nervous system have been challenging and remain to be addressed. Our previous studies have demonstrated that hyaluronic acid (HA) has good neuroinflammation resistance, 20 as well as suitable biocompatibility in many biomedical applications 21–27 . Studies have shown that mitochondrial abnormalities are the leading cause of ROS accumulation in the nervous system 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, protecting polyphenols in vivo and delivery to the nervous system have been challenging and remain to be addressed. Our previous studies have demonstrated that hyaluronic acid (HA) has good neuroinflammation resistance, 20 as well as suitable biocompatibility in many biomedical applications 21–27 . Studies have shown that mitochondrial abnormalities are the leading cause of ROS accumulation in the nervous system 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have demonstrated that hyaluronic acid (HA) has good neuroinflammation resistance, 20 as well as suitable biocompatibility in many biomedical applications. 21 , 22 , 23 , 24 , 25 , 26 , 27 Studies have shown that mitochondrial abnormalities are the leading cause of ROS accumulation in the nervous system. 28 Further, our recent studies found that HA can reduce ROS and restore neural damage by protecting the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Zhang et al designed a nanoparticles delivery system targeting different stages of osteoclasts, and confirmed that the system could effectively target the corresponding osteoclasts. 69 However, our delivery system may be inferior to other engineering sEVs system in terms of biocompatibility and the loading efficiencies of specific miRNA, as reported previously. 70 Therefore, the system exhibited the following advantages: (1) it is the first system to target osteoclast precursors to reduce VPA-associated side-effects on bone.…”
Section: Discussionmentioning
confidence: 64%
“…Both nanoparticles were modified with CD44-binding hyaluronic acid (HA), which further fostered delivery to the CD44-rich bone marrow. 343 The targeting ability of both nanoparticles on bone resorption areas was validated by bone tissue sectioning and small animal biopsy.…”
Section: Bone Matrixmentioning
confidence: 99%